Legal Protection of Cryptocurrency Users Against Cybercrime Attacks - Adi Darmawansyah; Djunaedi Djunaedi; Kristiawanto Kristiawanto (International Journal Labs, 2023)
The medium of exchange can be any object that can be accepted by everyone in society in the process of exchanging goods and services. Long before knowing money, humans had made transactions using barter practices, that is, the exchange of goods and/or services for the desired goods and/or services. In the preparation of this research, a normative juridical approach where approach is carried out based on the main legal material by examining theories, concepts, legal principles, and laws and regulations related to this research. Cryptocurrency assets don't just impact people who mine or trade crypto. It turns out that anonymous platforms that run crypto are also increasingly associated with cybercrime. A recent study from Interisle Consulting Group revealed that phishing attempts related to cryptocurrencies grew 257 percent compared to last year (compared to a 61 percent increase in phishing attacks overall), especially for attacks on wallets and exchanges. The rapid development of information and communication technology makes the journey of the development of crime in the virtual and digital world (cybercrime) sophisticated and complex.